Development Trends of Bilingual Tatar Lexicography of the XXI Century - SIBGAEVA, FIRUZA RAMZELOVNA; SAGDATZYANOVNA NURMUKHAMETOVA, RAUSHANIYA; SATTAROVA, MADINA RASHIDOVNA; UDERBAYEV, ALMAS ZHAUYNBAYEVICH (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article is devoted to a brief overview of bilingual dictionaries of Tatar language of the 21st century, in particular 2000-2017. The main objective of this study is to define the basic tendencies of development of Tatar bilingual lexicography of the new century, which develops mainly according to a traditional direction that was laid by the lexicographers of the 19th–20th centuries: published translation dictionaries for the general population and for highly specialized industries. The study provides the author's classification of printed translation dictionaries related to a selected segment of the history of Tatar lexicography.RESUMEN El artículo está dedicado a una breve reseña de los diccionarios bilingües de la lengua tártara del siglo XXI, en particular 2000-2017. El objetivo principal de este estudio es definir las tendencias básicas de desarrollo de la lexicografía bilingüe tártara del nuevo siglo, que se desarrolla principalmente de acuerdo con una dirección tradicional que trazaron los lexicógrafos de los siglos XIX-XX: diccionarios de traducción publicados para la población en general y para industrias altamente especializadas. El estudio proporciona la clasificación del autor de los diccionarios de traducción impresos que están relacionados con un segmento seleccionado de la historia de la lexicografía tártara.